2020
DOI: 10.35848/1882-0786/abacdf
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional isotope effect on transition temperature in BiS2-based superconductor Bi4O4S3

Abstract: We report the sulfur isotope effect on transition temperature in a BiS2-based superconductor Bi4O4S3. Polycrystalline samples of Bi4O4S3 were prepared using 32 S and 34 S isotope chemicals.From magnetization analyses, the isotope exponent (S) was estimated as -0.1 < S < 0.1.Although the Tc estimated from electrical resistivity was scattered as compared to those estimated from the magnetization, we observed no clear correlation between Tc and the isotope mass. The present results suggest that unconventional p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…As summarised in Fig. 1, isotope effect suggesting the importance of phonon was observed for the high-P phase of (Sr,La)FBiS 2 , whereas unconventional isotope effects were observed in La(O,F)BiSSe and Bi 4 O 4 S 3 26,27 . Although there are some possible factors, which could affect isotope effect, other than pairing states 32 , we consider that the observed difference in isotope effect is essentially caused by the different pairing states between those systems.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…As summarised in Fig. 1, isotope effect suggesting the importance of phonon was observed for the high-P phase of (Sr,La)FBiS 2 , whereas unconventional isotope effects were observed in La(O,F)BiSSe and Bi 4 O 4 S 3 26,27 . Although there are some possible factors, which could affect isotope effect, other than pairing states 32 , we consider that the observed difference in isotope effect is essentially caused by the different pairing states between those systems.…”
Section: Discussionmentioning
confidence: 89%
“…Conventional shifts in T c between samples synthesised with 32 S and 34 S were observed, which suggests the importance of phonons for the pairing mechanisms in the compound. The conventional isotope effects in (Sr,La)FBiS, which has a monoclinic structure, are in contrast to the unconventional isotope effects observed in La(O,F)BiSSe and Bi 4 O 4 S 3 , which have a tetragonal structure 26,27 . Based on a combination of the discussion of previous and present isotope studies, we suggest that the structural difference between the tetragonal and monoclinic structures could be a switch of the pairing mechanisms in BiCh 2 -based superconductors.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…However, an angle-resolved photoemission spectroscopy (ARPES) study reported the observation of the anisotropic superconducting gap, indicating that unconventional superconductivity is emerging in NdO 0.71 F 0.29 BiS 2 [10]. Furthermore, the absence of isotope effects was observed in tetragonal LaO 0.6 F 0.4 Bi(S,Se) 2 , which was examined using 76 Se and 80 Se isotopes [11], and Bi 4 O 4 S 3 , which was examined using 32 S and 34 S isotopes [12]. These results also imply that unconventional pairing is essential for BiCh 2 -based superconductors with a tetragonal structure.…”
Section: Introductionmentioning
confidence: 94%
“…Similar high-pressure effects with the structure change have been observed in various BiS2-based superconductors, such as EuFBiS2 [14] and Ce(O,F)BiS2 [15], suggesting a common mechanism for Tc enhancement. According to an investigation of isotope effects, the high-pressure phase of (Sr,La)FBiS2 with a monoclinic crystal structure exhibits conventional-type Tc shifts by substituting 32 S and 34 S [16], unlike the unconventional isotope effects observed in La(O,F)Bi(S,Se)2 [7] and Bi4O4S3 [17] with tetragonal structures. The high-pressure approach is also beneficial for inducing superconductivity in BiS2-based compounds, such as NdO0.8F0.2Sb1-xBixSe2 (x = 0 to 0.8) [18] and EuFBiS2 [19].…”
mentioning
confidence: 99%